PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS V SDN CANDIPARI 1 SIDOARJO - DWI CAHYANI, SINTA; SUKIDI, MASENGUT (PGSD FIP UNESA, 2018)
This research aims to know the influence of media use a picture writing poetry against students of class V SDN Candipari 1 Sidoarjo. This research data collection methods are either 6, namely, test validity, reliability test, test, test the normality of its homogeneity, test a hypothesis, test N-Gain ternormalisasi. The results showed that the calculation of T-Test using SPSS Analysis 22. The result of the calculation is the value of the Sig (2-tailed) of 0.000. The results of the sig (2-tailed) for 0.000 which means that this value smaller than 0.05 where it can be concluded that the Ha is received and Ho is rejected. The results of the calculation of the N-ternormalisasi gain control class shows numbers 0.32 meaning in the category of low gain and n class experiment of 0.75 which means high in the category they have the sense that there is influence by the existing use media picture against the skills of writing a poetry. Keywords: Media Picture, writing skills a poetry.